Signature of rigidity percolation effect in dielectric behavior of germanium containing multi-component chalcogenide glasses (ChGs). Issue 13 (September 2019) - Pal, Shiv Kumar; Kumar, Amit; Mehta, N.
Abstract: To develop new chalcogenide glasses (ChGs) as dielectric materials having a high dielectric constant and low dielectric loss, some quaternary glasses have been prepared from a novel third-generation Se–Te–Sn-Ge (STSG) system. This study reveals the effect of Ge addition on the dielectric relaxation and thermally activated a.c. conduction in a ternary ChG of Se–Te–Sn (STS) system. The compositional variation of the various dielectric and electrical parameters in the present STSG chalcogens rich non-oxide glasses Se78-y Gey Te20 Sn2 (0 ≤ y ≤ 6) has been investigated. The results show that Ge plays a potential role in improving the dielectric properties of the parent STS glass. The dielectric relaxation and thermally assisted a.c. conduction have been investigated by examining the frequency/temperature dependence of dielectric constant/loss. The absence of the dielectric relaxation for the higher concentration of Ge indicates that the relationship of microstructure and dielectric properties can be explained in terms of the stiffness transition followed by the self-organization of the corner sharing and the edge-sharing arrangements of GeSe4 phase.